Pengaruh Terapi Kombinasi Musik Alam dan Suling Terhadap Tingkat Kecemasan Ibu Bersalin Kala I - Hati, Devi Permata; Purwanti, Dwi; Islamiah, Ahdatul; Nugrahini, Evi Yunita (Jurnal Kebidanan Malakbi, 2025)
Anxiety is a common psychological disturbance experienced by mothers during the first stage of labor, with a particularly high prevalence. This condition is primarily triggered by the intensity of pain and various other psychological and physical stressors, which can negatively impact the progression of labor. Immediate intervention is therefore crucial to mitigate potential risks to both maternal and fetal safety. The study's theoretical basis posits that therapeutic sounds, such as nature and flute music, can stimulate the hypothalamus, which in turn regulates the body's stress response and leads to a reduction in cortisol levels. This physiological change was hypothesized to directly mitigate the psychological distress and anxiety experienced by laboring women. This research aimed to analyze the effect of a combined nature and flute music therapy on anxiety levels in women during the first stage of labor. A one-group pre-test/post-test design was implemented, and the study's population consisted of women in the first stage of labor at TPMB Afah Fahmi. A purposive sampling technique was used to select a sample of 31 respondents based on specific criteria. The independent variable was the music combination, and the dependent variable was the anxiety level, which was measured using the PASS questionnaire. The results demonstrated a significant effect of the intervention (p=0.000). Before the therapy, the majority of participants experienced moderate anxiety, which dramatically decreased following the intervention, with nearly half of the respondents reporting only mild anxiety. In conclusion, the combination of nature and flute music serves as an effective, non-pharmacological intervention for reducing anxiety. It is recommended that future studies conduct larger, controlled trials to further investigate this therapy and its potential for broader application in maternal healthcare.